Drug-Induced Intersticial Nephritis. Clinical Case - Tekoriutė, Paulina; Matuliauskaitė, Monika; Jonaitis, Laimas Virginijus (Acta medica Lituanica, 2021)
5-Aminosalicylic acid (5-ASA) preparations are widely used in the treatment of inflammatory bowel diseases. The most commonly used medicine is mesalamine. Overall, it is a very safe drug with few side effects. A rare side effect of this medicine is interstitial nephritis (IN). With discontinuation of the drug the renal function usually restores. However, if damage has not been detected for a long time, irreversible changes may occur. In this article, we present a clinical case of mesalamine induced IN. A 56-year-old man who has had ulcerative colitis for 20 years, was admitted due to mesalamine induced acute renal failure. A year before, the patient had been diagnosed with mesalamine-induced interstitial nephritis and the treatment with mesalamine was discontinued. The symptoms of ulcerative colitis worsened, and the patient independently decided to start taking mesalamine, which resulted in worsening of his health condition and impaired renal function. Mesalamine has been discontinued, additional treatment for acute kidney failure has been administered including hemodialysis. Renal function recovered and the patient was released for further treatment of ulcerative colitis and monitoring of renal function.